2021
DOI: 10.1007/s11605-021-04994-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of Removed Lymph Nodes on the Prognosis of M0 Small-Bowel Neuroendocrine Tumors: a Propensity Score Matching Analysis from SEER Database

Abstract: Background Current studies on the number of removed lymph nodes (LNs) and their prognostic value in small-bowel neuroendocrine tumors (SBNETs) are limited. This study aimed to clarify the prognostic value of removed LNs for SBNETs. Methods SBNET patients without distant metastasis from 2004 to 2017 in the SEER database were included. The optimal cutoff values of examined LNs (ELNs) and negative LNs (NLNs) were calculated by the X-tile software. Propensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…After matching, our results showed that the surgical approach, tumor size, sex, race, income, TNM stage, and tissue type were not correlated with either DSS or OS, but the tumor grade was correlated with prognosis ( P < 0.006), in line with the findings reported by Margonis et al 14 , and patients aged less than 60 years had better 5-year OS than those aged older than 60 years ( P = 0.001). In view of surgical resection is too aggressive and accompanied by serious surgical risks for the local disease, endoscopic treatment, as the main treatment method for tumors ≤ 1 cm, has the significant advantages of a short operation time, low cost, short hospital stay, and low impact on quality of life 7 , 8 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After matching, our results showed that the surgical approach, tumor size, sex, race, income, TNM stage, and tissue type were not correlated with either DSS or OS, but the tumor grade was correlated with prognosis ( P < 0.006), in line with the findings reported by Margonis et al 14 , and patients aged less than 60 years had better 5-year OS than those aged older than 60 years ( P = 0.001). In view of surgical resection is too aggressive and accompanied by serious surgical risks for the local disease, endoscopic treatment, as the main treatment method for tumors ≤ 1 cm, has the significant advantages of a short operation time, low cost, short hospital stay, and low impact on quality of life 7 , 8 .…”
Section: Discussionsupporting
confidence: 91%
“…P < 0.05 was considered statistically significant (two-tailed tests). The MatchIt package of R software v3.6.3 ( https://www.R-project.org ) was used to perform 1:1 PSM with a caliper value set to 0.1 for sex, race, income, tumor size, T stage, N stage, M stage, TNM stage and histologic type 14 . The nearest-neighbor matching method was used to match the baseline characteristics between the two groups.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure the accuracy and generality of the results, patients were randomly divided into training and validation cohorts, and then clinical cure and nonclinical cure groups were matched by PSM for baseline imbalance. This method can simulate randomized controlled trials well and improve the reliability of the results ( 20 ). There were significant differences between the clinically cured and noncured groups in age, sex, race, tumor location, surgical methods, and histologic type.…”
Section: Discussionmentioning
confidence: 99%
“…40 Additional studies have demonstrated that the number of lymph nodes removed has prognostic significance, with better survival in patients who underwent a more extensive lymphadenectomy. [41][42][43] The lack of hierarchical prognostication by stage group observed in the AJCC survival analysis may be caused by insufficient lymph node dissection, leading to inaccurate staging.…”
Section: Ileal/jejunal Netsmentioning
confidence: 99%
“…A retrospective study on 691 patients with jejunal‐ileocecal NETs found no significant difference in survival between stage I/II and III midgut NETs, with further analysis showing that, among patients who had stage III NETs, 5‐year survival for those with resectable tumors who also underwent a lymph node dissection was significantly better than for those whose tumors were unresectable 40 . Additional studies have demonstrated that the number of lymph nodes removed has prognostic significance, with better survival in patients who underwent a more extensive lymphadenectomy 41–43 . The lack of hierarchical prognostication by stage group observed in the AJCC survival analysis may be caused by insufficient lymph node dissection, leading to inaccurate staging.…”
Section: Site‐specific Changes In Ajcc Versionmentioning
confidence: 99%